The dynamic centres of infrared-dark clouds and the formation of cores - Rigby, Andrew J.; Peretto, Nicolas; Anderson, Michael; Ragan, Sarah E.; Priestley, Felix D.; Fuller, Gary A.; Thompson, Mark A.; Traficante, Alessio; Watkins, Elizabeth J.; Williams, Gwenllian M (Monthly notices of the Royal Astronomical Society, 2024)
High-mass stars have an enormous influence on the evolution of the interstellar medium in galaxies, so it is important that we understand how they form. We examine the central clumps within a sample of seven infrared-dark clouds (IRDCs) with a range of masses and morphologies. We use 1-pc-scale observations from the Northern Extended Millimeter Array (NOEMA) and the IRAM 30m telescope to trace dense cores with 2.8-mm continuum, and gas kinematics in C18O, HCO+, HNC, and N2H+ (J = 1-0). We supplement our continuum sample with six IRDCs observed at 2.9 mm with the Atacama Large Millimeter/submillimeter Array (ALMA), and examine the relationships between core- and clump-scale properties. We have developed a fully automated multiple-velocity component hyperfine line-fitting code called mwydyn which we employ to trace the dense gas kinematics in N2H+ (1-0), revealing highly complex and dynamic clump interiors. We find that parsec-scale clump mass is the most important factor driving the evolution; more massive clumps are able to concentrate more mass into their most massive cores - with a log-normally distributed efficiency of around 9 per cent - in addition to containing the most dynamic gas. Distributions of linewidths within the most massive cores are similar to the ambient gas, suggesting that they are not dynamically decoupled, but are similarly chaotic. A number of studies have previously suggested that clumps are globally collapsing; in such a scenario, the observed kinematics of clump centres would be the direct result of gravity-driven mass inflows that become ever more complex as the clumps evolve, which in turn leads to the chaotic mass growth of their core populations.